2014
DOI: 10.12927/hcpol.2014.23783
|View full text |Cite
|
Sign up to set email alerts
|

Income and Regional Gradients in Being without a Regular Doctor: Does the Slope of Gradients Decrease for Those with Greater Health Needs?

Abstract: Objective: Income and regional gradients in being without a regular family doctor have been reported. The study objective was to assess the extent to which the slopes of both income and regional gradients vary by individuals' health needs. Method: Using the Canadian Community Health Survey and multivariate regression analyses, the study examined the income and interprovincial variations in potential access among the healthy and less healthy populations. Results: The presence of chronic conditions was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…For team-based primary care physician access, we found that immigrants, refugees, and people residing in urban areas were substantially less likely to have access to team-based primary care. Similar gaps in primary care access have been consistently documented in the general population, in Canada and internationally (Exworthy et al, 2006;Glazier, Zagorski, & Rayner, 2012;Hay et al, 2010;Reid et al, 2009;Sepehri, 2014;Ssendikaddiwa et al, 2023;Talbot et al, 2001;Viera et al, 2006). Reasons behind these disparities are likely multifactorial but may be influenced by Ontario's primary care payment system.…”
Section: Discussionmentioning
confidence: 65%
“…For team-based primary care physician access, we found that immigrants, refugees, and people residing in urban areas were substantially less likely to have access to team-based primary care. Similar gaps in primary care access have been consistently documented in the general population, in Canada and internationally (Exworthy et al, 2006;Glazier, Zagorski, & Rayner, 2012;Hay et al, 2010;Reid et al, 2009;Sepehri, 2014;Ssendikaddiwa et al, 2023;Talbot et al, 2001;Viera et al, 2006). Reasons behind these disparities are likely multifactorial but may be influenced by Ontario's primary care payment system.…”
Section: Discussionmentioning
confidence: 65%